Street-Level Bureaucracy and Government Transformation - Mandario, Rionarda Raja Ramdhani; Pratono, Alusius Hery (International Journal Labs, 2023)
This article aims to examine how the policy transformation deals with the risk of government failure at the street-bureaucracy level. The researchers adopt a qualitative research method to address the question by seeking an in-depth understanding of a case study of the licensing process in Lombok Island, Indonesia. Researchers collect data through interviews, observations, and document analysis to understand the case comprehensively by focusing on government transformation process. The results show the policy transformation deals with the risk of government failure at the street-bureaucracy level by shaping the organizational culture, gaining support from various stakeholders, sharing valuable resources, and reforming the day-to-day administration. This study extends the emerging literature on street-level bureaucracy.